Análise de contingência com critério N – 1linhas e compensação de reativos em linhas de transmissão - Onorio, Haline Raissa Paulas (2022)
With the steady growth in demand for electricity, studies focused on the area of control and operation of the system become imperative in terms of ensuring quality, reliability, security and safety in energy supply. This work aims to carry out contingency studies on transmission lines with N – 1lines criterion in three national subsystems, equivalent, referring to the South, Southeast and MatoGrosso (STB107CA) and the evaluation of possible shunt compensation in order to minimize the overloading of the transmission lines and ensure the voltage stability in the bars after the contingency. Aiming at careful analyses in relation to the place to receive compensation andthe amount tobe allocated, the optimization of the power flowwas performed considering two objective functions, maximum power transfer and voltage control. Regarding contingency analysis, four scenarios were achieved: a first in which convergence could not be achieved, another of cases that resulted in violation of the power flow, cases that resulted in violation of voltageand finally, cases that didnot present violations in the analyzed parameters of the system. In this aspect, it was also possible to evaluate that the transmission capacity of a line, when beyond its limit, results in the drop of the voltage along the adjacent lines. As well as it found that contingency cases that resulted in breaches of the power flow, occurred mostly in system regions in which the connection between buses was performed onlythrough the contingent line, in whichits compromise results in overloading the power flow of neighboring lines. Reactive compensation showed significant results when applied to elimination of voltage violationand recovery of post contingency voltage levels, however, wasnot very relevant when the elimination or even minimization of power flow violations was applied.